Strategic foresight an introduction to managing organizational change: An exploratory study of the opinions of a sample of administrative leaders in the Salah al-Din Health Department - Hife, Amar Hmood; Muhameed, Kefah Abbas (Tikrit Journal of Administrative and Economic Sciences, 2022)
The research aims to identify the role of strategic foresight in promoting the process of organizational change, using the questionnaire as a main tool for collecting data and information related to the research and related to the field aspect. In the administrative administration, (4) forms were completely retrieved, including invalid ones, with a response rate (97.2%) of the total distributed forms, and the analysis was done by the statistical program (SPSS-V.23). The strategic and organizational change in by giving some delegation of powers in order to provide sufficient flexibility in the organizational structure to accommodate future changes Which plays its role in increasing opportunities for creativity and development in the field of health work.